Carotid Intima Media Thickness Is Independently Associated with Male Gender, Middle Age, and IGF-1 in Metabolically Healthy Obese Individuals. (28th January 2014) - Abd El-Hafez, Hala; Elrakhawy, Mohamed M.; El-Baiomy, Azza A.; El-Eshmawy, Mervat M.
Abstract : Background/Aims . The effect of benign obesity on subclinical cardiovascular disease is still questionable. The purpose of this study was to assess carotid intima media thickness (CIMT), as a marker of subclinical atherosclerosis, and to evaluate its relation to age, sex, and IGF-1 in metabolically healthy obese (MHO) subjects. Methods . A total of 75 MHO subjects and 80 age, and sex matched healthy nonobese control subjects were included in the study. Body mass index (BMI), waist circumference (WC), blood pressure, fasting plasma glucose, fasting insulin, HOMA-IR, lipid profile, insulin like growth factor-1 (IGF-1), and CIMT were assessed in all subjects. Results . MHO subjects had significantly higher CIMT and lower IGF-1 than healthy nonobese controls. Mean CIMT was significantly higher in MHO men age subgroup range from 30 to 50 years than in their age range matched (premenopausal) MHO women subgroup. In MHO subjects, CIMT was positively correlated with age, BMI, WC, SBP, HOMA-IR, TG, and LDL-C, and negatively correlated with IGF-1. Regression analysis revealed that middle age, male sex and IGF-1 remained independently associated with CIMT in MHO subjects. Conclusion . CIMT is elevated and IGF-1 is reduced in MHO subjects, and CIMT is independently associated with male gender, middle age, and IGF-1. Definition of healthy obesity may be broadened to include IMT measurement.